2009
DOI: 10.1673/031.009.2701
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Cauline Domatia of Two Newly Discovered Ecuadorian Ant Plants inPiper: An Example of Convergent Evolution

Abstract: The stems of some myrmecophytes in Piper are used as domatia by resident ant colonies. Hollow, ant-occupied stems were previously known only in four species of southern Central American Piper, all members of Section Macrostachys. Here we present two additional, unrelated, hollow-stemmed myrmecophytes from Ecuador: P. immutatum and P. pterocladum (members of sections Radula and Peltobryon, respectively). Although similar superficially, stem cavities of the Ecuadorian Piper species differ morphologically and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This study exclusively includes observations and experiments involving this species of ant from P. immutatum. The stems are hollowed out by the ants, and the plants produce food bodies early in plant development (Tepe et al 2009). This adaptation is known from other myrmecophytic Piper species that produce food bodies when ant colonies are present (Risch et al 1977, Risch & Rickson 1981.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study exclusively includes observations and experiments involving this species of ant from P. immutatum. The stems are hollowed out by the ants, and the plants produce food bodies early in plant development (Tepe et al 2009). This adaptation is known from other myrmecophytic Piper species that produce food bodies when ant colonies are present (Risch et al 1977, Risch & Rickson 1981.…”
Section: Methodsmentioning
confidence: 99%
“…Pheidole-Piper interactions, in which the Piper plant provides shelter in the form of domatia and food in the form of food bodies, have been documented for five Piper species in Costa Rica (Tepe et al 2007) and two in the northeastern Andes of Ecuador (Tepe et al 2009). Several studies in lowland forests have demonstrated that Pheidole ants have an indirect positive effect on Piper cenocladum biomass and fitness through decreasing herbivory by Eois (Geometridae) caterpillars and other herbivores (Letourneau 1983(Letourneau , 1998.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…), the petiole flattens laterally into a photosynthetic organ, the phyllode (Dong and He 2017 ). Others have swollen petioles with cavities inhabited by ants, such as in Piper cenocladum (Tepe et al 2009 ). Additionally, food bodies, which are structures that may contain proteins, lipids, or carbohydrates in different proportions and serve to maintain mutualistic relationships between the plant and ants, occur at specialized sites called trichilia at the swelling petiole-stem juncture in Ceropia obtusa (Bell and Bryan 2008 ; Marting et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Kelley spent a good portion of his career focusing on taxonomy within the genus Cryptantha ( Boraginaceae ; e.g., Kelley and Wilken 1993 ), but became fascinated with Piper when he visited Costa Rica in 1997 to work with Piper species at La Selva Biological Station. He was interested generally in angiosperm evolution, evolution of unique morphologies, stem anatomy, and tropical biology and spent years working with Piper from Costa Rica and Ecuador (e.g., Tepe et al 2009 ). He examined the unique morphology of Piper , and documented Piper stem anatomy.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%